Difference in Total Serum Immunoglobulin E Level Among Patients With and Without Intravenous Contrast Media Adverse Reaction on Computed Tomography Scan Examination (Sumatera Medical Journal, 2019)
The adverse reaction (AR) to intravenous contrast media (ICM) are relatively common. Various opinions pro-posed in the mechanism of the incidence of ICM AR. Suspected that the role of Immunoglobulin E (IgE) me-diates allergic conditions that are part of the AR. Objective:To determine the difference in total serum IgE level  among subjects with and without ICM AR on computed tomography (CT) scan examination. To ob-serve difference in total serum IgE levels in subjects undergoing ICM adverse reaction based on the degree of severity. Method: An analytical study with cross-sectional design of 104 subjects undergoing CT scans with ICM, examined IgE levels before and after ICM was administered, then measured the severity of adverse  re-actions of contrast media. Result: In this study, subjects undergoing adverse reactions, prior to administration Iopamidol  had a higher mean IgE 1270.79 mg / dl compared with those who having AR  1174.90 mg / dl and after administration of Iopamidol  a mean of Ig E is still higher in subjects having AR  1507.96 mg/dl com-pared with those having negative AR that is 1325.88 mg/dl, p = 0.696, statistically, not significant. Mild reac-tions in 40 subjects (38.5%) with cough, nausea, dizziness, itching, and sweating. Conclusion: Increase in total IgE levels in subjects with positive adverse reactions are independent(p=0.696).